Multimodal Nonlinear Microscopy by Shaping a Fiber Supercontinuum From 900 to 1160 nm - Liu, Yuan (2011)
Nonlinear microscopy has become widely used in biophotonic imaging. Pulse shaping provides control over nonlinear optical processes of ultrafast pulses for selective imaging and contrast enhancement. In this study, nonlinear microscopy, including two-photon fluorescence, second harmonic generation, and third harmonic generation, was performed using pulses shaped from a fiber supercontinuum (SC) spanning from 900 to 1160 nm. The SC generated by coupling pulses from a Yb:KYW pulsed laser into a photonic crystal fiber was spectrally filtered and compressed using a spatial light modulator. The shaped pulses were used for nonlinear optical imaging of cellular and tissue samples. Amplitude and phase shaping the fiber SC offers selective and efficient nonlinear optical imaging over a broad bandwidth with a single-beam and an easily tunable setup.